Recent advancements and comprehensive analyses of butyric acid in cardiovascular diseases - Xu, Qiang; Liu, Xiaomin; Wang, Zhengming; Li, Xianghui; Jiang, Qianfeng; Xu, Min (Frontiers in Cardiovascular Medicine, 2025)
Cardiovascular disease (CVD) remains a predominant cause of morbidity and mortality globally, characterized by pathological mechanisms that encompass inflammation, oxidative stress, metabolic disturbances and immune dysregulation. Recently, the influence of gut microbiota and its metabolites on the onset and progression of CVD has garnered significant attention. Short-chain fatty acids (SCFAs), particularly butyrate, are the primary products of gut microbial fermentation of dietary fiber. Butyrate is instrumental in maintaining intestinal barrier function and immune homeostasis and exhibits notable anti-inflammatory, antioxidant, and metabolic regulatory potentials in cardiovascular diseases. Nonetheless, the precise molecular mechanisms of butyrate in various cardiovascular diseases and its clinical translational value necessitate a systematic review of the literature. This study conducted a comprehensive search of databases, such as PubMed and Web of Science, to synthesize recent basic and clinical research on butyrate and cardiovascular diseases, focusing on its role in hypertension, atherosclerosis, coronary artery disease, atrial fibrillation, diabetic cardiomyopathy, and heart failure. The findings indicate that butyrate can influence cardiovascular health through multiple pathways, including the modulation of G protein-coupled receptors (GPCRs), histone deacetylases (HDACs), and peroxisome proliferator-activated receptors (PPARs). Although numerous experimental studies have corroborated the protective effects of butyrate in cardiovascular diseases, its clinical translation remains challenging owing to factors such as optimal administration route, dose optimization, and individualized treatment strategies. Future research should integrate large-scale population cohort analyses and randomized controlled trials (RCTs) to ascertain the precise efficacy of butyrate in the prevention and treatment of cardiovascular diseases and explore its potential as a novel therapeutic target.